Estratégias de adubação no controle de plantas daninhas em sistemas integrados de produção agropecuária - Correia, Éder Sequini (2022)
The objective of this work was to evaluate the effect of NPK fertilization strategies on pasture and soybean crop in integrated agricultural production systems (LPIS) as a possible way to control weeds and their effects on animal weight gain and soybean productivity. The experiment was established in 2020 with the sowing of pasture (Urochloa brizantha, cv. BRS Piatã) after the harvest of the soybean crop (Glycine max, cv. BRASMAX Ultra IPRO) which is implanted annually in October in a no-tillage system. The experimental design was in randomized blocks, with four fertilization strategies: (1) conventional fertilization (phosphate and potassium in the soybean crop AC - N), (2) conventional fertilization + nitrogen fertilization in the pasture (AC + N), (3) Pasture fertilization (phosphate and potassium in the AP - N pasture phase) and (4) System fertilization (phosphate, potassium and nitrogen in the AS pasture phase). The amounts of fertilizers applied were 100 kg of nitrogen ha-1 (320 kg ha-1 of ammonium nitrate) in a single dose on the pasture, the phosphate and potassium fertilization was 72 kg of P2O5 ha-1 and 90 kg of K2O ha-1. The height of the pasture was regulated by means of rotational grazing and variable stocking rate in the treatments, with an average of 3.5 AU/ha, of Nelore beef steers aged 13 to 24 months, entry with 40 cm of height. of the pasture, on 03/21/2020, removed 30 cm high from the pasture, on 07/17/2020. In the treatments that were carried out with the fertilization of NPK (AS) and PK systems without N in the pasture phase (AP-N), there was a significant reduction in the population and phytomass of the four main weed species collected: Digitaria horizontalis (Capim-colchão), Eleusine indica (Chen-foot grass), Chamaesyce hirta (Santa Luzia herb), Cyperus aggregatus (Cyperus). Nitrogen fertilization as a weed management strategy and increases in animal and soybean production is only justified when phosphate and potassium fertilization is applied in the crop phase. Fertilization of NPK systems on pasture increases soybean productivity, while animal weight gain is higher with PK fertilization on soybean with N on pasture. The repositioning of phosphate and potassium fertilization in the pasture phase is sufficient for the management of weeds both in the pasture and in the crop phase.